Mutations in PYCR1 cause cutis laxa with progeroid features - Reversade, Bruno; Escande-Beillard, Nathalie; Dimopoulou, Aikaterini; Fischer, Björn; Chng, Serene C; Li, Yun; Shboul, Mohammad; Tham, Puay-Yoke; Kayserili, Hülya; Al-Gazali, Lihadh; Shahwan, Monzer; Brancati, Francesco; et al. (Nature genetics, 2009)
Stefan Mundlos and colleagues report the identification of mutations in PYCR1 that cause autosomal recessive cutis laxa. PYCR1 encodes an enzyme involved in proline metabolism and localizes to mitochondria. Autosomal recessive cutis laxa (ARCL) describes a group of syndromal disorders that are often associated with a progeroid appearance, lax and wrinkled skin, osteopenia and mental retardation 1 , 2 , 3 . Homozygosity mapping in several kindreds with ARCL identified a candidate region on chromosome 17q25. By high-throughput sequencing of the entire candidate region, we detected disease-causing mutations in the gene PYCR1 . We found that the gene product, an enzyme involved in proline metabolism, localizes to mitochondria. Altered mitochondrial morphology, membrane potential and increased apoptosis rate upon oxidative stress were evident in fibroblasts from affected individuals. Knockdown of the orthologous genes in Xenopus and zebrafish led to epidermal hypoplasia and blistering that was accompanied by a massive increase of apoptosis. Our findings link mutations in PYCR1 to altered mitochondrial function and progeroid changes in connective tissues.